Terapi Dzikir terhadap Tingkat Stres pada Pasien Gagal Jantung Kongestif - Raka Maya Daud; Asep Suryadin; Tri Utami; Dhinny Novryanthi (Journal of Telenursing (JOTING), 2026)
This study aims to analyze the effect of dhikr therapy on stress levels in patients with congestive heart failure (CHF). The research method used was a pre-experimental study with a one-group pretest–posttest design. The results showed that the average stress score before dhikr therapy was 25.82 ± 4.64 and decreased to 14.76 ± 3.41 after the intervention. Statistical tests showed a significant effect of dhikr therapy on stress levels in CHF patients with a p-value <0.001. In conclusion, dhikr therapy has been shown to reduce stress levels in patients with congestive heart failure significantly. It can be used as a non-pharmacological nursing intervention to support holistic nursing care.   Keywords: CHF, Dhikr, Spiritual Nursing, Stress